Memory Effect of Bacteria‐Killing Properties of Piezo‐Catalysts Nanomaterials through Defect Engineering - Omid Amiri; Karzan A. Qurbani; Karukh A. Babakr; Peshang Kh. Omer; L. Jay Guo; Hastyar Hama Rashid Najmuldeen; Martin Bertau; Peshawa H. Mahmood; Sangar S. Ahmed; Mohammed A. Jamal (Advanced NanoBiomed Research, 2025)
This study investigates the effects of piezo‐catalysts on sterilizing surfaces. The memory effects in three piezo‐catalysts, ZnO, CuO, and SiO2 are discovered, which are produced by a calcination process. After applying mechanical force to these materials, they retain an antibacterial effect for a period of days. With this discovery, it is possible to combat antibiotic‐resistant bacteria by using piezo materials on hospital floors or operating rooms that can kill bacteria just by walking on them. The results show that ZnO, CuO, and SiO2 are capable of killing bacteria even after being subjected to mechanical force for 9 days. The memory effect duration can be influenced by a variety of factors, including the calcination temperature, the storage condition after ultrasonication, the drying temperature after ultrasonication, and the solvent in which the piezo‐catalyst is ultrasonicated. When ZnO, CuO, and SiO2 are kept under a vacuum in a dark environment, the piezo effect remains almost constant for 11 days after sonication.